Parental perception and knowledge of sound and noise pollution in learning environment at home - Mohd Sabidi, Anis Syuhada; Ismail, Noraidah (IIUM PRESS, 2024)
Background: Noise pollution poses increasing concerns for health and learning, with parental knowledge playing a critical role in managing noise levels in children’s home learning environments. Objective: This study evaluates parents' perceptions and knowledge of noise pollution in their children's study spaces. Method: A cross-sectional design was employed, and convenience sampling was used to select 144 Malaysian parents of school-aged children. A questionnaire was administered to assess their views on noise sources and management practices in home learning environments. All data were analysed via SPSS (Version 20). Results: While 87.5% of parents enforced sound-level rules, only 44.4% recognised noise as a health risk, indicating limited awareness. Mann-Whitney U test showed no significant difference in noise awareness between parents of different educational levels (p=0.247). Conclusion: The findings reveal critical gaps in parental awareness regarding noise’s health impacts, highlighting the need for educational programs to help parents create quieter, more supportive learning environments for children.